Perancangan Media Kampanye Program “Cegah Stunting, Itu Penting!” oleh Puskesmas Pasirjambu Kabupaten Bandung - Nichi Hana Karlina; Mohamad Hilman Suparman (Universitas Informatika dan Bisnis Indonesia, 2024)
Stunting is a condition of growth failure in toddlers due to chronic malnutrition, resulting in children being too short for their age. UPTK Puskesmas Pasirjambu recorded cases of stunting during the year 2022, with 77 out of 608 toddlers measured for their height experiencing stunting. Although the program